Mesoporous silica nanoparticles: a smart nanosystem for management of breast cancer. Issue 2 (February 2018) - Poonia, Neelam; Lather, Viney; Pandita, Deepti
Highlights: Stimuli-responsive MSNs can release drug at a target site by smart signal switching. MSNs possess great potential for better diagnosis of breast cancer. Multifunctional MSNs provide solutions for multidrug resistance issues. Improved breast cancer therapy using targeted MSNs. Abstract : Breast cancer is the second-leading cause of death in women worldwide owing to aggressive metastasis, lack of early diagnosis and poor access to treatment amenities. During the past decade, mesoporous silica nanoparticles (MSNs) have gained ground for the delivery of a wide variety of chemotherapeutic and bioimaging agents owing to their unique characteristics and straightforward fabrication methods. Present research studies based on MSNs have provided various potential insights in their applicability in breast cancer treatment by improving solubility and stability and decreasing the adverse effects of current treatment regimens. This review focuses on the applicability of this novel modality in the management of breast cancer. Teaser: Inorganic nanoparticles paving the way for better management of breast cancer.